Students’ ethnographic practices reflect critical conscious research in a multicultural college class - Pace, Josefa (Journal of Interdisciplinary Studies in Education, 2019)
Teaching the Issues in Multicultural Education course at a New York State college with a diverse population highlights the necessity to address current complex societal topics. The course’s methodological framework is ingrained in the democratic ideas of tolerance, justice, and agency. This article describes an interdisciplinary college course, which allows students to practice ethnographic methods in order to re-conceptualize and confront stereotypes and social constructions. Through a formal mini ethnographic project, students documented their observations and interactions of a religious institution within a community. The oral and written presentations from this field-based research displayed that students became critically conscious of others’ communal practices when they investigated the sites from a first-hand account.